2010
DOI: 10.1002/ptr.3148
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of dietary ginger on muscle pain induced by eccentric exercise

Abstract: Zingiber officinale, commonly known as ginger, has analgesic and antiinflammatory properties. The acute effects of ginger on muscle pain, inflammation and dysfunction induced by eccentric exercise were examined. Twenty-seven participants performed 24 eccentric actions of the non-dominant elbow flexors. In a double-blind, cross-over design, participants ingested a 2 g dose of ginger or placebo 24 h and 48 h after exercise. Pain intensity (0-100 mm), arm volume (water displacement), range-of-motion (goniometry) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 27 publications
(52 reference statements)
4
26
0
Order By: Relevance
“…It is also possible that the ginger constituents have a limited window of antiinflammatory function, such that termination of ginger supplementation removed the protective effect against muscle damage. This is consistent with data from Black (Black and O'Connor, ), whereby individuals who received 2 g of ginger 24 h after an eccentric muscle damage protocol exhibited reduced pain the following day, whereas individuals ingesting placebo did not. While previous studies found ginger supplementation relieved pain associated with eccentric damage (Black et al, ; Black and O'Connor, ), the VAS data from this study did not.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It is also possible that the ginger constituents have a limited window of antiinflammatory function, such that termination of ginger supplementation removed the protective effect against muscle damage. This is consistent with data from Black (Black and O'Connor, ), whereby individuals who received 2 g of ginger 24 h after an eccentric muscle damage protocol exhibited reduced pain the following day, whereas individuals ingesting placebo did not. While previous studies found ginger supplementation relieved pain associated with eccentric damage (Black et al, ; Black and O'Connor, ), the VAS data from this study did not.…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with data from Black (Black and O'Connor, ), whereby individuals who received 2 g of ginger 24 h after an eccentric muscle damage protocol exhibited reduced pain the following day, whereas individuals ingesting placebo did not. While previous studies found ginger supplementation relieved pain associated with eccentric damage (Black et al, ; Black and O'Connor, ), the VAS data from this study did not. It is possible that continued ginger supplementation is necessary for an analgesic effect.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In healthy controls, ginger has been shown to reduce muscle soreness 113 and muscle pain following exercise. 114 Ginger also reduces pain in patients with moderate to severe dysmenorrhea 115 and osteoarthritis 116 (see Ref. 117 for a review).…”
Section: Gingermentioning
confidence: 98%
“…Despite some research examining ginger as an analgesic for resistance-training-induced soreness, 12,15 no studies have examined whether ginger root reduces muscle soreness and improves muscle function in the context of endurance training and competition. Given that NSAIDs can cause substantial adverse effects, additional research is needed to evaluate the analgesic properties of alternative compounds, including nutraceuticals.…”
mentioning
confidence: 99%